Characterization of two proline-rich proteins involved in silicon deposition in Cucummis sativus - Sun, Hao; Gao, Feijuan; Kong, Xiaoping; Jiao, Zhen; Tan, Zhongfang; Wu, Jie; He, Bochao; Duan, Yaoke (Frontiers in Plant Science, 2025)
IntroductionSilicon can exert benefits on plants when they are suffering stresses, and the benefits are more obvious in high silicon accumulators. However, the molecular mechanism how silicon deposits in plants is not fully understood.MethodsThis study identified the CsPRP family genes in cucumber, and analyzed their functions in cucumber silicon deposition via expression in Escherichia coli. Additionally, their intracellular localization was analyzed via transient expression of green fluorescent protein (GFP) fusion constructs in onion epidermal cells, and their expression profiles were characterized using ProCsPRP1::GUS and ProCsPRP3::GUS transgenic Arabidopsis.Results and DiscussionSeven PRP genes were identified in cucumber, of which CsPRP1 and CsPRP3 were identified as tandem duplication, CsPRP4 and CsPRP5 were identified as segmental duplication. The binding experiment of silicon showed that both CsPRP1 and CsPRP3 exhibited significant binding characteristics to silicon, but their optimal pH values were different. Transient expression in onion epidermal cells revealed that CsPRP1 and CsPRP3 were specifically localized on the cell wall. Staining of ProCsPRP1::GUS and ProCsPRP3::GUS transgenic Arabidopsis demonstrated that during the seedling phase, CsPRP1 and CsPRP3 were mainly expressed in the mature leaves and roots, and in the mature phase, they were mainly expressed in the leaves, roots, petals and stamens. These results may aid further research into the biological function of cucumber PRP and the molecular mechanism of silicon deposition in cucumber.